Resilience of national team student football players with different life values - Khokhlova N.I. ,; Muller O.Yu. ,; Rodermel T.A. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the multidimensional relationship between the levels of life values and resilience of student football players. Methods and structure of the study. Students of the national football team took part in the empirical study. The methods of “Vitality Test” by S. Maddi were used in the Russian adaptation by D.A. Leontyev and E.I. Rasskazova, “Morphological test of life values” V.F. Sopov and L.V. Karpushina. Results and conclusions. The systematic involvement of students in sports activities actualizes the development of values and determines personal meanings. The results obtained allow us to conclude that the development of student sports and the involvement of students in active sports activities is one of the conditions for the formation of a stress-resistant personality. Social support, common activities, and joint solution of problem situations in a sports game mutually determine a high level of resilience.